Pengaruh model science, environment, technology, society (sets) terhadap pengembangan kecerdasan interpersonal siswa kelas IV pada pembelajaran IPA - Siti Nur Azizah; Kun Hisnan Hajron; Dhuta Sukmarani (Universitas Muhammadiyah Magelang, 2023)
Intelligence develops according to the environment that influences an individual. Then it is this intelligence that makes the difference between one individual and another. This intelligence is important in life because basically humans cannot live alone. Humans are social creatures who are always in contact with other people. Relationships with people around, of course, communicate with each other which is the basis for interaction between individuals because basically communication is very intertwined with interpersonal relationships. However, it is unfortunate that children's interpersonal intelligence is still very low, due to a lack of interaction with peers, teachers, and the environment, so they feel isolated. People who are belittled have negative characteristics such as being aggressive, difficult to cooperate with, and a lack of sympathy and empathy. That way it is necessary to do a research in order to improve and realize preventive efforts. The purpose of this study was to implement the Science, Environment, Technology, Society (SETS) model for the development of interpersonal intelligence in grade IV students in science learning. The research method used in this study was quantitative with a pre-experimental approach with fourth grade students at Balerejo State Elementary School. Based on the results of the research and discussion, students must establish good relationships with other people, have a sense of empathy and sympathy and be able to maintain good friendships with friends. That way, it is highly recommended for teachers to develop interpersonal intelligence by applying model sets.